The effect of language contact on Romance verbal paradigms: an empirical survey - Luís, Ana R. (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
Rather than conveying morphosyntactic meaning, conjugation classes determine how such properties are expressed. Conjugation classes are therefore ‘ornamental’ properties of language and clearly not essential to communication. Such purely formal distinctions tend to be absent from contact varieties largely because adults have a natural tendency to bypass linguistic features that are perceived as semantically unnecessary (e.g., Seuren and Wekker 1986, McWhorter 2001). The goal of this paper, however, will be to show that language contact does not necessarily lead to a loss of meaningless forms. Building on recent work by Luís (2008, forthcoming), we provide empirical evidence which shows that Romance conjugation classes respond in different ways to language contact. In particular, we show that conjugation classes may undergo different types of morphological change, such as lexicalization, levelling, retention and extension. Our evidence will be drawn from contact varieties which have derived from the contact between one Romance language (either Portuguese or Spanish) and one (or more than one) non-Romance language.